2018
DOI: 10.1093/ntr/nty029
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cognitive Control in the Self-Regulation and Reinforcement of Smoking Behavior

Abstract: Cognitive control (CC) - the ability to regulate attention and memory - plays an important role in a variety of health behaviors, including smoking behavior. In this theoretical review of the literature, we propose a CC and smoking behavior framework that includes 1) the positive influence of CC on the self-regulation of smoking; 2) nicotine-induced improvements in CC that may indirectly reinforce smoking (including withdrawal reversal effects); and 3) the long-term effects of smoking on the brain that may res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 112 publications
1
8
0
1
Order By: Relevance
“…Self-regulation means a tendency to control internal modes, control momentums, and behaviours, and adapt them to criteria to achieve the goal 36 . Consistent with the results of our study, the study by Evans et al 37 showed that students who had less self-regulated feelings than other students had a higher chance of starting smoking. Regarding the lack of studies in the field of the role of selfregulation in WPS, it seems that using the selfregulating process in students can create changes in them and direct them in reaching their goal, so that the probability increases for their behaviour to change to reduce waterpipe.…”
Section: Discussionsupporting
confidence: 93%
“…Self-regulation means a tendency to control internal modes, control momentums, and behaviours, and adapt them to criteria to achieve the goal 36 . Consistent with the results of our study, the study by Evans et al 37 showed that students who had less self-regulated feelings than other students had a higher chance of starting smoking. Regarding the lack of studies in the field of the role of selfregulation in WPS, it seems that using the selfregulating process in students can create changes in them and direct them in reaching their goal, so that the probability increases for their behaviour to change to reduce waterpipe.…”
Section: Discussionsupporting
confidence: 93%
“…And the local administration of nicotine into the substantia nigra can appear the activation of the nAChRs, namely a4b2 and a7, on dopaminergic nerve terminals in the corpus striatum [ 23 ], And it was also well documented that the number of 3[H] nicotine binding sites, a4b2 nAChRS, are increased in the brains of smokers examined postmortem [ 24 26 ]. In addition to potential neuroprotective behaviors, from learning and memory enhancement to addiction and neuroprotection, nicotine also has antidepressant properties and the ability to improve cognitive activities such as attention [ 27 ] and cognitive control [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine also has a protective effect on dopaminergic neurons. In addition to potential 111 neuroprotective behaviors, from learning and memory enhancement to addiction and 112 neuroprotection, nicotine also has antidepressant properties and the ability to improve 113 cognitive activities such as attention (DAJASBAILADOR, 2004) and cognitive 114 control (Evans, To, & Ashare, 2018). 115 On the one hand, studies on the long-term effect of smoking have shown smoking impaired attention ability (Due et al, 2002), we expect that smoking aggravates attention and neural impairment in COPD patients with a smoking comorbidity.…”
Section: Introductionmentioning
confidence: 99%